2020
DOI: 10.3390/molecules25092171
|View full text |Cite
|
Sign up to set email alerts
|

A New Oleanane Type Saponin from the Aerial Parts of Nigella sativa with Anti-Oxidant and Anti-Diabetic Potential

Abstract: Natural product studies explore potential and interesting new compounds to discover innovative drugs. Nigella sativa (N. sativa) (Ranunculaceae) is traditionally used to treat diabetes. Flavonoids and triterpenoid mostly show anti-diabetic activity. The current study aim to identify new compounds by a systematic study of the anti-oxidant and anti-diabetic activity of aerial parts of N. sativa concerning. Phytochemicals were isolated from the methanolic extract of aerial parts of the plant by column chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…Natural products and their derivatives are rich sources of active and novel compounds that may be used against several adverse conditions including cancers, diabetes, inflammatory diseases, metabolic diseases, neurological diseases, and many others [ 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. NO, a unique biological neurotransmitter, is involved in the initiation of several biological and pathological conditions, including immunomodulation, inflammation, and neuronal transmission in the central and peripheral nervous systems, which may lead to neurological disorders.…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…Natural products and their derivatives are rich sources of active and novel compounds that may be used against several adverse conditions including cancers, diabetes, inflammatory diseases, metabolic diseases, neurological diseases, and many others [ 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. NO, a unique biological neurotransmitter, is involved in the initiation of several biological and pathological conditions, including immunomodulation, inflammation, and neuronal transmission in the central and peripheral nervous systems, which may lead to neurological disorders.…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…The chemical complexity of saponins is described as the gap between understanding the relationship between their structures and the relative pharmaceutical and medicinal properties [39]. Various activities have been attributed to these glycosides, such as anti-diabetic, anti-inflammatory [40][41][42], anti-tumour and anti-bacterial activities [43]. In this study, 19 saponins were identified, including cycloartane triterpenoids.…”
Section: Major Chemical Classes Of Momordica Metabolomesmentioning
confidence: 94%
“…Inhibition of peroxidase activity is another benefit of flavonoids, which allows the prevention from oxygen reactive species [ 18 ]. Among the extracted phenolic compounds from the NS seeds ( Figure 2 ), we mention gallic acid, ferulic acid, vanillic acid, p-coumaric acid, chlorogenic acid, catechin, quercetin, apigenin, rutin, nigelflavonoside B, and flavone [ 19 , 20 ].…”
Section: Nigella Sativa Phytochemistrymentioning
confidence: 99%
“…Between the years 1985 and 1995 different NS alkaloids were isolated and identified ( Figure 3 ) such as nigellicine which is composed of an indazole nucleus [ 21 ], nigellimine which is an isoquinoline molecule [ 22 ], also nigellimine N-oxide, and finally nigellidine which is a molecule of indazole nature [ 23 ]. While another molecule called magnoflorine was recently identified in the aerial part of the NS plant [ 20 ].…”
Section: Nigella Sativa Phytochemistrymentioning
confidence: 99%